PENGARUH USER EXPERIENCE, ACCURACY OF RESPONSES, PERSONALIZATION USER ENGAGEMENT DAN RETENTION CHATGPT - Ulfah Zulkarnain, Nadia; Osly Usman; Annisa Lutfia (CV. KAMPUSA AKADEMIK PUBLISING, 2025)
This study aims to analyze the influence of user experience, accuracy of responses, and personalization on user engagement and its impact on user retention in the context of ChatGPT usage. A quantitative approach was employed by distributing questionnaires to 200 active ChatGPT users and analyzing the data using path analysis with the help of SmartPLS software. The results show that all three main variables—user experience, accuracy of responses, and personalization—have a positive and significant effect on user engagement. Furthermore, user engagement significantly affects user retention. These findings highlight that a positive user experience, accurate responses, and relevant personalization features are crucial in building user engagement and loyalty toward artificial intelligence-based systems such as ChatGPT.